2014
DOI: 10.1002/maco.201307497
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion potential and cathodic reduction efficiency of stainless steel in natural seawater

Abstract: Stainless steels are widely used for different applications in seawater in the oil and gas and desalination industries. It is well known that the corrosion potential of stainless steel shifts to the noble direction (ennoblement) when exposed to natural seawater. The other significant effect of the biofilm on metallic surfaces is a dramatic increase of the cathodic reduction efficiency (e.g. cathodic reduction of dissolved oxygen), promoting the corrosion reactions and increasing the rate of corrosion propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…In this study, we were interested in gaining further insight into the bacterial community of the stainless-steel surface immersed in seawater and its electrochemical activity in relation to the potential ennoblement. Previous studies have shown an inhibition of the ennoblement activity above a critical temperature (Scotto et al, 1986; Dupont et al, 1997; Martin et al, 2003; Gümpel et al, 2006; Thierry et al, 2015). In our setting, this critical temperature was between 38°C and 40°C, above which the ennoblement was inhibited despite the continuing presence of bacteria.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, we were interested in gaining further insight into the bacterial community of the stainless-steel surface immersed in seawater and its electrochemical activity in relation to the potential ennoblement. Previous studies have shown an inhibition of the ennoblement activity above a critical temperature (Scotto et al, 1986; Dupont et al, 1997; Martin et al, 2003; Gümpel et al, 2006; Thierry et al, 2015). In our setting, this critical temperature was between 38°C and 40°C, above which the ennoblement was inhibited despite the continuing presence of bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Kinetically, an increase of the cathodic reaction rate can also result in an increase of the OCP. Previous works have demonstrated that surface microorganisms increase cathodic reduction efficiency (Johnsen and Bardal, 1985; Holthe et al, 1989; Audouard et al, 1994; Zhang and Dexter, 1995; Mollica and Scotto, 1996; Rogne and Steinsmo, 1996; Le Bozec et al, 2001; Larché et al, 2011; Thierry et al, 2015). Other reactions such as manganese oxide reduction in freshwater (Dickinson and Lewandowski, 1996; Gümpel et al, 2006) and the formation of hydrogen peroxide could also contribute to the increase of the OCP as it is a stronger oxidant than oxygen with a higher redox potential (Landoulsi et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preliminary experiment (Chapter 3 section 3.2.1), following immersion in seawater, the OCP of super duplex stainless steel (SD) increased and reached ~ 270 mV in 2 d and remained stable for 7 d. This was consistent with experiments in tropical environments, where SD initially showed ennoblement at approximately 300 mV in 3-5 d of immersion and remained stable until 50 d, (Thierry et al 2014). Xu et al (2015) also observed potential ennoblement for SS316L immersed in natural seawater.…”
Section: Corrosion Behavior During the Initial Stage Of Micsupporting
confidence: 70%
“…S1B, curve a), the potential of the electrode reached values comprised between +450 and +650 mV vs SHE. Such potential values in natural (non-sterile) waters are often interpreted as oxygen reduction potential of biocathode developed on stainless steel [28,29]. Note that no corrosion was observed during the three months of this experiment.…”
Section: Preliminary Evaluation Of Materialsmentioning
confidence: 94%